Mass-spectrometry phytochemical profiling of Etlingera coccinea (Blume) S. Sakai & Nagam from Sabah - Helmy Abdellah Nazeer, Nurfateen; Ag Nuddin, Julenah; Salim, Fatimah (Faculty of Applied Sciences, 2025)
Etlingera coccinea (Blume) S. Sakai & Nagam is classified in the genus of the Etlingera (Zingiberaceae). Locally known as ‘tuhau’ in Sabah, it is used as traditional remedy such as to cure food poisoning, stomachache as well as condiment in cooking. Previous studies on the genus Etlingera have focused on its phytochemical compounds and biological activities. However, mass-spectrometric profiling of crude extracts has not been reported. In this research, E. coccinea stalks were taken from two different localities: Ranau and Tambunan areas to determine their chemical profiles. Each of locations have three types of crude fractions: n-hexane, chloroform and methanol. The phytochemical screening for both locations shows the presence of flavonoids, terpenoids and tannins. Through detailed chemical profiling, the library of Liquid Chromatography Mass-Spectrometry (LC-MS) analysis results showing 10 and 8 known metabolites found in Ranau methanolic, and chloroform extracts respectively. While for Tambunan methanolic and chloroform extracts, 8 and 4 known metabolites found. Additionally, Gas Chromatography Mass-Spectrometry (GC-MS) analysis reported 15 and 9 known metabolites respectively from Ranau and Tambunan nhexane extracts. All identified phytochemical compounds have their own potential application such as antibacterial, anti-fungal, antioxidants, anti-inflammatory, and anti-cancer. The roles could serve as a basis for further exploration of the chemical composition as well as the biological activities of E. coccinea.